The Philippines through the lens of an American soldier (1898-1907) the Harry Whitfield Harnish photographic collection - Lico, Gerard Rey A.; Harnish, Harry Whitfield; Philippines. National Commission for Culture and the Arts.; University of the Philippines Diliman. Library; Art Studies Foundation; University of the Philippines (Diliman).; University of the Philippines (Diliman). Office for Initiatives in Culture and the Arts.; University of the Philippines (Diliman). College of Architecture. Studio Laboratory on Architectural History, Theory and Criticism ([Manila] National Commission for Culture and the Arts, University of the Philippines Library, and Art Studies Foundation, 2004)
Contains digital reproduction of Harnish's photographic works which were taken in the Philippines between 1898 and 1907, from the collection of the University of the Philippines Library.
Title from disc label.
Gerard Rey A. Lico, project director/ editor-in-chief.
System requirements: Pentium 200 or higher; 64MB RAM; Win 98, 2000, ME, XP.
Keywords: Harnish, Harry Whitfield -- 1869-1960 -- Photograph collections; Philippines -- History -- 1898- -- Pictorial works; Photography -- Negatives -- Catalogs; Philippines -- Pictorial works -- Catalogs